2017
DOI: 10.1094/phyto-11-16-0396-r
|View full text |Cite
|
Sign up to set email alerts
|

Rare Pyrenophora teres Hybridization Events Revealed by Development of Sequence-Specific PCR Markers

Abstract: Pyrenophora teres f. teres and P. teres f. maculata cause net form and spot form, respectively, of net blotch on barley (Hordeum vulgare). The two forms reproduce sexually, producing hybrids with genetic and pathogenic variability. Phenotypic identification of hybrids is challenging because lesions induced by hybrids on host plants resemble lesions induced by either P. teres f. teres or P. teres f. maculata. In this study, 12 sequence-specific polymerase chain reaction markers were developed based on expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Chromosomal rearrangements driven by TE expansion can reduce fertility and contribute to reproductive isolation ( Delneri et al, 2003 ; Coghlan et al, 2005 ). In the case of P. teres , the expansion of repetitive elements in PTT has not yet contributed to chromosomal rearrangements between the two forms, so low rates of survival of natural hybrids between the forms in the field ( Poudel et al, 2017 ) cannot be explained by such rearrangements. The viability of PTT/PTM hybrids is therefore more likely due to unequal recombination events leading to deleterious gene loss or gain, or a fitness penalty associated with incompatibility between new gene combinations, or another yet to be determined mechanism rather than large-scale genome dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomal rearrangements driven by TE expansion can reduce fertility and contribute to reproductive isolation ( Delneri et al, 2003 ; Coghlan et al, 2005 ). In the case of P. teres , the expansion of repetitive elements in PTT has not yet contributed to chromosomal rearrangements between the two forms, so low rates of survival of natural hybrids between the forms in the field ( Poudel et al, 2017 ) cannot be explained by such rearrangements. The viability of PTT/PTM hybrids is therefore more likely due to unequal recombination events leading to deleterious gene loss or gain, or a fitness penalty associated with incompatibility between new gene combinations, or another yet to be determined mechanism rather than large-scale genome dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Although artificial hybrids can be readily made in the laboratory ( McDonald, 1967 ; Smedegård-Petersen, 1977a ; Campbell and Crous, 2003 ; Jalli, 2011 ), PTT and PTM are considered to be genetically autonomous populations ( Rau et al, 2003 , 2007 ; Bakonyi and Justesen, 2007 ; Bogacki et al, 2010 ; Lehmensiek et al, 2010 ; Leišová-Svobodová et al, 2014 ; Akhavan et al, 2016 ). Natural hybrids appear to be rare and have been suggested by RAPD and AFLP studies ( Campbell et al, 2002 ; Leišova et al, 2005 ; McLean et al, 2014 ), and recently confirmed by Poudel et al (2017) using form-specific markers. However, a lack of field hybrids suggests a natural barrier to fertility as found by Smedegård-Petersen (1977a) or a fitness penalty.…”
Section: Introductionmentioning
confidence: 91%
“…1C and D). Thus, the DLA-spray method will be useful for determining the virulence and lesion types of laboratory-generated hybrid forms (Poudel et al 2017) while keeping the isolates confined in a laboratory biosafety cabinet.…”
Section: Discussionmentioning
confidence: 99%
“…The progeny of these recombinants have been referred to as hybrids. Hybrids have also been successfully produced in laboratory culture (Campbell et al 1999;Poudel et al 2017). The intact-seedling assay is currently the standard method for phenotyping net blotch of barley (Arabi et al 1991;Sharma 1984;Xi et al 1999).…”
mentioning
confidence: 99%
“…P. teres has two forms with similar morphologies but with distinct disease symptoms [11,12]. The two forms are largely genetically autonomous, although rare hybridisation events can occur [13][14][15][16]. In barley, P. teres f. teres (Ptt) causes net form net blotch (NFNB) and P. teres f. maculata (Ptm) spot form net blotch (SFNB).…”
Section: Introductionmentioning
confidence: 99%